Maria Iracema Bezerra Loiola (2013) A new species of Erythroxylum (Erythroxylaceae) from the Brazilian semiarid region. Phytotaxa 150(1): 61–64. - Loiola, Maria Iracema Bezerra (Phytotaxa, 2013)
The illustration presented in this paper does not correspond to Erythroxylum angelicae, but the other new species being described from Brazil. The correct figure is shown as below.